Analisis Sikap Berbudi Luhur Melalui Filosofi Memayu Hayuning Bawono Perspektif Kontruksi Sosial Peter Ludwig Berger (Studi Kasus di PSHT Komisariat IAIN Ponorogo) - Habib Mujahidin Ma’sum; Abu Muslim (Yayasan Dinamika Ilmu Banyuwangi, 2025)
The background of the problem at PSHT Komisariat IAIN Ponorogo is the lack of understanding about noble character attitudes and behavior among its members. PSHT members tend to have attitudes that do not fully reflect the noble values inherent in the teachings of Setia Hati Terate martial arts. The cause of this problem is that members often feel superior due to their martial arts training, which involves physical and mental discipline, leading to a sense of being the best among others. Martial arts teachings typically incorporate noble values that have been guiding principles for centuries, given that martial arts are a national heritage worth preserving. To address the lack of awareness among members about the importance of noble character attitudes, PSHT Komisariat IAIN Ponorogo incorporates habituation practices that implement noble character attitudes through the philosophy of